Perception of emotions across Portuguese varieties - Santos, Diana; Cruz, Marisa (Frontiers in Communication, 2026)
This study investigates the perception of emotional prosody across two major varieties of Portuguese—Brazilian (BP) and European (EP)—examining how differences in their intonational systems and cultural backgrounds shape emotion recognition. Building on theoretical frameworks of vocal emotion, an experiment was designed using acoustically controlled, acted stimuli expressing neutrality, happiness, sadness, and anger. Native listeners from both varieties completed a perception task measuring identification accuracy and reaction times. Results revealed a clear emotion hierarchy: neutrality and sadness were recognized most accurately and rapidly, whereas happiness and anger were frequently confused, indicating higher perceptual ambiguity. While both listener groups showed a native-variety advantage, EP participants demonstrated superior overall accuracy, attributed to greater exposure to BP media, and more consistent cue reliance. These findings highlight the interplay between universal acoustic cues, variety-specific phonological structuring, and cultural exposure in shaping emotional speech perception. This research contributes to prosodic typology in Portuguese, cross-variety speech perception, and the integration of linguistic and affective models, with implications for phonological theory, applied technologies, and communication in general.